Analisis Strategi Pemasaran dalam Meningkatkan Omzet Penjualan di Howie Coffee & Eatery Surabaya - Olivia, Jessica; Moeheriono; Winarto (Journal Of Accounting and Business, 2023)
Choosing the right marketing strategy can help every business actor not only to face any existing obstacles but also to develop a business so that it can develop for the logterm. Currently, the world of coffee shops is on the rise, many business actors are completing to establish a coffee shop business. In addition, with the growth of the world of coffee shop that are increasingly developing, people lifestyles have changed, which at first just enjoyed the available menu, but then urned into a new habit every day. This study uses a qualitative case study method. Data collection used in this study using interviews, documentation, and observation. Based on the results of the discussion above, it can be concluded that the results of the SWOT analysis of Howie Coffee & Eatery Surabaya are in quadrant I, which means that the situation is very profitable because it can use force to take advantage of existing opportunities. For the internal category with a strength score of 2.05 and a weakness score of 1.06. while for the external category with an opportunities score of 2.01 and a weakness score of 1.47 it produces coordinate points (1.12:0.94). So the strategy used is the SO (Strength-Opportunity) strategy and there are several alternative strategies than can later be useful for Howie Coffee & Eatery Surabaya, namely as follows: (1).Maintain product quality and improve service quality to increase customer loyalty, (2). Continue to innovate products according to trend developments. (3). Maintain good relations with suppliers in order to maintain price quality and product quality, (4). Utilizing technological developments for promotion and development facilities